Wrenches in the works: drug discovery targeting the SCF ubiquitin ligase and APC/C complexes - Cardozo, Timothy (BioMed Central, 2007)
Recently, the ubiquitin proteasome system (UPS) has matured as a drug discovery arena, largely on the strength of the proven clinical activity of the proteasome inhibitor Velcade in multiple myeloma. Ubiquitin ligases tag cellular proteins, such as oncogenes and tumor suppressors, with ubiquitin. Once tagged, these proteins are degraded by the proteasome. The specificity of this degradation system for particular substrates lies with the E3 component of the ubiquitin ligase system (ubiquitin is transferred from an E1 enzyme to an E2 enzyme and finally, thanks to an E3 enzyme, directly to a specific substrate). The clinical effectiveness of Velcade (as it theoretically should inhibit the output of all ubiquitin ligases active in the cell simultaneously) suggests that modulating specific ubiquitin ligases could result in an even better therapeutic ratio. At present, the only ubiquitin ligase leads that have been reported inhibit the degradation of p53 by Mdm2, but these have not yet been developed into clinical therapeutics. In this review, we discuss the biological rationale, assays, genomics, proteomics and three-dimensional structures pertaining to key targets within the UPS (SCF(Skp2 )and APC/C) in order to assess their drug development potential. Publication history: Republished from Current BioData's Targeted Proteins database (TPdb; ).